Does Acupuncture Protect Dopamine Neurons in Parkinson's Disease Rodent Model?: A Systematic Review and Meta-Analysis - Ko, Jade Heejae; Lee, Hyangsook; Kim, Seung-Nam; Park, Hi-Joon (Frontiers in Aging Neuroscience, 2019)
Background: Acupuncture has been reported to have significant effects, not only in alleviating impaired motor function, but also rescuing dopaminergic neuron deficits in rodent models of Parkinson's disease (PD). However, a systemic analysis of these beneficial effects has yet to be performed. Objective: To evaluate the neuroprotective effect of acupuncture in animal models of PD. Methods: A literature search of the PubMed, MEDLINE, EMBASE, China National Knowledge Infrastructure, Research Information Service System, and Japan Society of Acupuncture and Moxibustion databases was performed to retrieve studies that investigated the effects of acupuncture on PD. The quality of each included study was evaluated using the 10-item checklist modified from the Collaborative Approach to Meta-Analysis and Review of Animal Data from Experimental Studies. RevMan version 5.3 (Foundation for Statistical Computing, Vienna, Austria) was used for meta-analysis. Results: The 42 studies included scored between 2 and 7 points, with a mean score of 4.6. Outcome measures included tyrosine hydroxylase (TH) level and dopamine content. Meta-analysis results revealed statistically significant effects of acupuncture for increasing both TH levels (33.97 [95% CI 33.15–34.79]; p < 0.00001) and dopamine content (4.23 [95% CI 3.53–4.92]; p < 0.00001) compared with that observed in PD control groups. In addition, motor dysfunctions exhibited by model PD animals were also mitigated by acupuncture treatment. Conclusions: Although there were limitations in the number and quality of the included studies, results of this analysis suggest that acupuncture exerts a protective effect on dopaminergic neurons in rodent models of PD.